Photophysical properties and excited state dynamics of 4, 7-dithien-2-yl-2, 1, 3-benzothiadiazole. Issue 21 (18th May 2017) - Iagatti, Alessandro; Patrizi, Barbara; Basagni, Andrea; Marcelli, Agnese; Alessi, Andrea; Zanardi, Stefano; Fusco, Roberto; Salvalaggio, Mario; Bussotti, Laura; Foggi, Paolo
Abstract : The relationships between the photophysics and structural properties of 4, 7-dithien-2-yl-2, 1, 3-benzothiadiazole as a function of solvent polarity are investigated both experimentally and by computational methods. Abstract : The relationships between the photophysics and structural properties of 4, 7-dithien-2-yl-2, 1, 3-benzothiadiazole as a function of solvent polarity are investigated both experimentally and by computational methods. Stationary fluorescence measurements are consistent with a model envisaging the presence of three types of conformers in equilibrium in the ground state. They are characterized by different relative orientations of the thiophene rings. Due to a low rotational barrier, the sample in solution is characterized by a distribution of relative internal orientations. By applying the Kawski method, we evaluate the average dipole moment of ground and excited states of the three types of conformers. The ground state dipole moments are small and similar for the three types of conformers. On the contrary, dipole moments differ substantially in the excited state. X-ray diffraction of a single crystal confirms the presence of an orientational disorder of thiophene rings. Transient absorption UV-visible spectroscopy experiments allows the identification of the main mechanisms responsible for the large Stokes shift observed in this push–pull molecule. Time dependent spectra provide a picture of the relaxation processes occurring after excitation: the primary step is an internal charge transfer assisted by thiophene ring planarization which occurs on a time scale ranging from 0.88 to 1.3 picoseconds depending on solvent polarity. Moreover, time-resolved fluorescence measurements are consistent with a mechanism involving planarization accompanied by a stabilization of the charge transfer state as observed in polar solvents. In the latter, longer fluorescence lifetimes are observed along with a quantum yield decrease due to the activation of specific non-radiative relaxation channels. The photophysical behavior of 4, 7-dithien-2-yl-2, 1, 3-benzothiadiazole in a solid matrix of polymethyl methacrylate is similar to that observed in solution, but the overall non-radiative process rate is slow with respect to that in the liquid phase. As a consequence, the radiative processes are enhanced giving rise to a fluorescence quantum yield of 90%. Such behavior is consistent with the proposed relaxation model.